Sri Lanka: Human Rights in the Context of Civil War - Cheran, Rudhramoorthy (Refuge: Canada's Journal on Refugees, 1999)
Violations of human rights in Sri Lankahave been fairly well documented.Unfortunately, the conflict in Sri Lanka,despite its intensity, has not attractedappropriate international attention. Thisarticle is a review of the current humanrights situation in Sri Lanka in the context of civil war.The article also evaluatesthe prospects for peace building amidstheightening ethnic tensions, emergencyregulations, and the lack of democraticgovernance in the southern part a regionwhich is outside the conflict zone.